Концептуальні засади визначення сутності толінгових операцій - Коць, І. І. (Видавництво Львівської політехніки, 2015)
Розглянуто та проаналізовано різні підходи до трактування понять “давальницька сировина”, “операції з давальницькою сировиною”, “толінг”, “толінгові операції” у теоретичній та нормативно-правовій базі. На цій основі концептуально обґрунтовано та сформульовано уніфіковані тлумачення сутності толінгу й толінгових операцій. Виокремлено та розкрито ключові характерні особливості толінгових операцій, що визначають специфіку їхнього здійснення. The actuality of research is caused by the fact that at present a major part of domestic enterprises is characterized by significant problems in the financial sphere and isn’t able to ensure its independent realization of manufacturing process for various reasons. In such conditions tolling operations are the one of the most attractive and perspective type of cooperation with the foreign partner, who is ready to give its own raw material, cover the production costs, provide product sales and pay for the performed processing work. Thus, the processing enterprise receives the perspective opportunities of improving the condition of its various problem spheres and further independent manufacturing of competitive products for the domestic and foreign markets. However, at modern stage there is no unified definition of the essence of the term “tolling operations”, as well as there are different approaches to its interpretation and analogization of tolling operations with the operations with raw materials in the scientific, legal and business fields. To eliminate the existing in categorical apparatus discrepancies and ambiguities on the problem of tolling operations the various approaches to the interpretations of the terms “raw materials”, “operations with raw materials”, “tolling” “tolling operations” in theoretical and legal basis are reviewed and analyzed. The received analysis results gave an opportunity to implement the conceptual grounding of essence of the key terms in tolling sphere. In particular, under the tolling operations it is proposed to understand the complex of inter-related jobs on processing raw materials (processing, assembly, disassembly, use, repair, modernization, reconstruction, etc.) of foreign customer (tollinger), which were imported into the country of performer (processing enterprise), with the aim to manufacture for him the finished product, which is subordinate to reexportation to the country of customer, on a contractual basis and in accordance with the valid norms of national and international law. In the article there are selected the key characteristics of tolling operations, which include: foreign economic character of tolling (the key participants in this process – the customer of finished product and its manufacturer must represent the different countries); legal nature of tolling (is based on the state regulation and control of the process realization and provides compliance with all valid legislative norms in this area); contractual nature of tolling (is based on an agreement between the contracting parties, which contains the conditions of process realization and obligations of subjects); constant nature of customer’s ownership on raw materials at any stage of its processing; pay character of tolling (provides the customer’s covering all costs which arise in the implementation of tolling operations and the compensation of performed work of processing enterprise); obligation of return of the made from customer’s raw materials production into his country.
Conceptual positions from defining the essence of tolling operations
Keywords: давальницька сировина; переробка; операції з давальницькою сировиною; толінг; толінгові операції; концепція; raw materials; processing; operations with raw materials; tolling; tolling operations; concept